Jual Beli Chips pada Game Online di Desa Sungai Jambat Kecamatan Sadu Menurut Perspektif Ekonomi Islam - Gusti Gusti; Daud Daud; Wandi Wandi; Kurniawan Kurniawan; Siti Fatimah; Haeran Haeran (Journal of Innovative and Creativity, 2025)
This study discusses the practice of buying and selling chips in online games that are rampant in Sungai Jambat Village, Sadu District, and is reviewed from an Islamic economic perspective. The rise of this activity is inseparable from the increasing use of smartphones and the internet among village communities, which makes online games a means of entertainment as well as a business opportunity. However, the practice of buying and selling chips carried out outside official channels raises a number of problems, such as elements of fraud, addiction, and indications of hidden gambling. In Islamic economics, transactions must meet the principles of justice, honesty, clarity of contracts, and be free from haram elements such as usury, gharar, and maysir. The results of the study show that the practice of buying and selling chips in the village is contrary to these principles, so it is not justified by sharia. Therefore, an active role is needed from the village government, religious leaders, and the community in providing education and creating alternative economic activities that are halal and beneficial.